A Critical Glance to Non-Pharmacological Management of Novel COVID-19 Infection: Non-Pharmacological Management of COVID-19 Infection - Saleem, Ayesha; Davis, Mariam; Rafique, Sadia; Meer, Sidra; Qader, Abdul; Aslam, Muhammad Nabeel (Pakistan Journal of Health Sciences, 2023)
Our study aim was to enhance awareness about the management of COVID-19 infection. Human health and way of life have been severely disrupted by corona virus disease-19 (COVID-19), a severe global public health emergency. While vaccines and cures are still being developed, the pandemic is still spreading. The main tools used to combat the COVID-19 infection are known as non-pharmacological interventions (NPIs), which have an impact on almost every aspect of social functioning. This review concentrated on identifying successful NPIs. Effective NPIs include isolation and quarantine, physical separation, and good hand hygiene. They should also be put into practice in light of the socioeconomic and cultural makeup of the population. UV light and public spraying of the outdoors are examples of ineffective NPIs. The optimum way to apply these measures is to apply them simultaneously or in combination. According to the findings, they have to be implemented early in the pandemic and for extended periods. The least amount of morbidity and mortality was achieved when vaccination was paired with strict NPI adherence. It has also been noticed that closing schools only work to contain COVID-19 when it is combined with thorough contact tracking. Determining how limiting NPIs will affect the number of cases and the categorization of COVID-19-related deaths is difficult. The design of the evidence for hygiene precautions like face masks is more solid and offers reliable information on COVID-19 infection prevention. These findings provide proof to support policy decisions about NPIs to prevent the COVID-19 pandemic from spreading.